2020
DOI: 10.1101/2020.06.29.178632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression ofblaOXA-58Gene Driven by ISAba3is Associated with Imipenem Resistance in a ClinicalAcinetobacter baumanniiIsolate from Vietnam

Abstract: AbstractThe aim of this study was to investigate genetic structures and expression of blaOXA-58 gene in five Acinetobacter baumannii clinical isolates recovered from two hospitals in southern Vietnam during 2012-2014. A. baumannii isolates were identified by automated microbiology systems and confirmed by PCR. All isolates were characterized as multidrug resistant by antimicrobials testing using th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…present, multidrug-resistant Acinetobacter infections are preferred to be treated with carbapenems [23], however, an elevated resistance rate to carbapenems has been reported worldwide, critically restricting the therapeutic choices. CRAB has long been regarded as concerned health problem, principally in economically developing nations [24]. Imipenem resistance was found in 72 of the 87 A.baumannii isolates (82.8 % ).…”
Section: Atmentioning
confidence: 99%
See 2 more Smart Citations
“…present, multidrug-resistant Acinetobacter infections are preferred to be treated with carbapenems [23], however, an elevated resistance rate to carbapenems has been reported worldwide, critically restricting the therapeutic choices. CRAB has long been regarded as concerned health problem, principally in economically developing nations [24]. Imipenem resistance was found in 72 of the 87 A.baumannii isolates (82.8 % ).…”
Section: Atmentioning
confidence: 99%
“…We found that blaVIM gene expression was higher than blaNDM and blaIMP gene expression cannot be detected. Previous studies investigated the gene expression of other carbapenemases [20,24]. CRAB strains overexpress blaOXA-23/ blaOXA-24, according to Nguyen et al [24].…”
Section: Atmentioning
confidence: 99%
See 1 more Smart Citation